Frontier issues of the political economy of migration - Gil S. Epstein (Institute for the Study of Labor (IZA), 2012)
Migration has a strong economic impact on the sending and host countries. Since individuals and groups do not benefit equally from migration, interest groups emerge to protect and take care of their narrow self-interests and compete for rents generated by migration. Narrow self-interests may be present not only for interest groups but also for ruling politicians and civil servants. In this paper we consider how political culture is important for determining policy and how interest groups affect, via a lobbying process, the choice of public policy. We also consider how interest groups and lobbying activities affect assimilation and attitudes towards migrants and international trade. The narrow interests of the different groups may cause a decrease in social welfare, in some cases, and may enhance welfare in other situations.
Keywords: F22; P48; O15; 330; migration; political economy; culture; minorities; politicians; Internationale Wanderung; Public Choice; Migrationspolitik; Interessenpolitik; Politische Kultur; Theorie; Welt